Strategy, structure, and performance of U.S. manufacturing and service MNCs: A comparative analysis - Habib, Mohammed; Victor, Bart (Strategic Management Journal, 1991)
Abstract This study analyzes the strategy‐structure fit and its effect on the economic performance of 144 U.S. manufacturing and service multinational corporations (MNCs). The results indicate that MNCs, irrespective of being services or manufacturing, choose their organization structure consistent with the theoretical fit prescription for the kind of strategy they are pursuing. However, the strategy‐structure fit had no effect on service MNC economic performance. With manufacturing MNCs, mixed results regarding the fit‐performance linkage were found. Based on the findings, implications and directions for future research are suggested.